2010
DOI: 10.1149/1.3484642
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oxygen Dissolution Rate from Gas Phase into Nafion Surface and Development of an Agglomerate Model

Abstract: To clarify the rate determining process for the oxygen transport in a catalyst layer of PEFCs, an oxygen dissolution resistance from gas phase into Nafion surface was measured. The oxygen dissolution resistance, which was estimated from the relationship between Nafion thickness on Pt electrode and the diffusion-limited current density on the electrode, was found to account for a large part of the total oxygen transport loss. By introducing the oxygen dissolution resistance, an agglomerate model was able to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 15 publications
8
75
1
Order By: Relevance
“…Therefore, high mass activity is necessary to decrease the Pt loading. However, electrochemical characterization of single cells 17 19 has revealed that high mass activity alone is not sufficient. For example, the characterizations by Greszler et al 19 demonstrated that decreased Pt loading is accompanied by an anomalous voltage drop owing to oxygen transport resistance in the cathode CL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high mass activity is necessary to decrease the Pt loading. However, electrochemical characterization of single cells 17 19 has revealed that high mass activity alone is not sufficient. For example, the characterizations by Greszler et al 19 demonstrated that decreased Pt loading is accompanied by an anomalous voltage drop owing to oxygen transport resistance in the cathode CL.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Morimoto et al have shown high resistivity of O 2 permeation through the ionomer layer, in particular at the catalyst/ionomer interface [29][30][31][32]. While the impact at high current densities is thought to be a major factor inhibiting further reductions in PGM content [3], these results show that even at OCP, O 2 permeability resistance is most likely a factor in the initial Nernst potential loss.…”
Section: Ex Situ Gde Measurementsmentioning
confidence: 96%
“…9,10,55 Since this overpotential occurs at high geometric current densities and low cathode rf values, i.e., at high local oxygen flux to the Pt surface, we hypothesize that it is related to oxygen transport limitations at the catalyst/ionomer interface. Suggestions for the observed voltage losses at high Pt-specific currents by other research groups include a limited dissolution of oxygen into the ionomer phase, 57 an intrinsically high transport resistance of the thin ionomer phase, 58 a limited effective ionomer surface, 10,37 or a decrease of the ORR kinetics at low potential. 59 Although we cannot exclude any one of these effects, a Pt/ionomer specific resistance appears most reasonable to explain the observed voltage losses at high Pt-specific currents, as the voltage profile shows a shape resembling a mass transport limitation, rather than a kinetic phenomenon.…”
Section: Ecsa Evolution During Voltage Cycling Asts-a Decrease Ofmentioning
confidence: 99%